Differences between the place of the match and ball possession in football league - Dizdar, D.; Basic, D.; Barisic, V. (Acta Kinesiologica, 2016)
Based on 88 matches in the 2014/2015 season of the first Croatian football league, a difference was determined to exist between the match place (hosts and guests) and ball possession. The results of t-test determined that the match place does not influence ball possession (p=0,38). This data shows that technical and tactical quality does not depend on the place that the match was played; more specifically, the teams do not adjust according to the place of match, because changes in the play need to be practiced over a longer time period.